Interparticle bonding and interfacial nanocrystallization mechanisms in cold sprayed metallic glass - Lupoi, Rocco (My University, 2022)
In this work, amorphous Zr-based bulk metallic glass deposit was manufactured by cold spray. The bonding mechanism of metallic glass particles was systematically investigated through studying the deformation behavior of individual particles after deposition or rebound. We revealed two collective particle bonding mecha- nisms that contributed to the formation of metallic glass deposit, i.e., high-velocity impact induced localized metal- lurgical bonding at the fringe of interface, and high gas-temperature induced partial melting of particles and result- ant annular metallurgical bonding band. Moreover, the dynamic evolution mechanism of amorphous phase into nanocrystal structures at severely deformed interfacial regions during cold spray was carefully investigated. For the first time, we observed different amorphous/nanocrystal structures in cold sprayed metallic glass particles, which can represent different evolution stages in nanocrystallization process. Based on the observation, it is inferred that the nanocrystallization process can be divided into following three stages: composition segregation, the formation of ordered 1D and 2D transition structures, and 3D nanocrystals. The current study provides new insights into bonding mechanisms and the mechanistic nanocrystallization origins in cold sprayed metallic glass.
International Thermal Spray Conference (ITSC)
Keywords: Metallic glass; Cold spray; Bonding